2008
DOI: 10.1038/bjp.2008.373
|View full text |Cite
|
Sign up to set email alerts
|

Protective action of doxycycline against diabetic cardiomyopathy in rats

Abstract: Background and purpose: Reactive oxygen and nitrogen species play an important role in the development of diabetic cardiomyopathy. They can activate matrix metalloproteinases (MMPs), and MMP-2 in particular is known to mediate early consequences of oxidative stress injury in the heart. Therefore, we investigated the role of MMP-2 and the effect of the MMP inhibitor doxycycline on the changes of heart function caused by diabetes. Experimental approach: Using streptozotocin-induced diabetic rats, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 50 publications
9
37
0
Order By: Relevance
“…Sodium selenate, (n-3) fatty acid, or doxycycline treatment of the rats for 4-week following diabetes induction preserved the basal value of diabetes-induced LVDP (50.5 ± 3.2 mmHg, 46.3 ± 4.2 mmHg, 43.7 ± 3.3 mmHg, respectively), significantly. As shown previously [3,14,15], other hemodynamic parameters of the diabetic hearts were also protected by these treatments, significantly. Since 4-week of sodium selenate, (n-3) fatty acid, or doxycycline treatment of the nondiabetic rats had no significant effect on the mechanical activity of the heart as well as the hemodynamic parameters [3,14,15], we did not measure any other parameters of the hearts into this study.…”
Section: Effects Of Either Antioxidants or Doxycycline Treatments On supporting
confidence: 85%
See 1 more Smart Citation
“…Sodium selenate, (n-3) fatty acid, or doxycycline treatment of the rats for 4-week following diabetes induction preserved the basal value of diabetes-induced LVDP (50.5 ± 3.2 mmHg, 46.3 ± 4.2 mmHg, 43.7 ± 3.3 mmHg, respectively), significantly. As shown previously [3,14,15], other hemodynamic parameters of the diabetic hearts were also protected by these treatments, significantly. Since 4-week of sodium selenate, (n-3) fatty acid, or doxycycline treatment of the nondiabetic rats had no significant effect on the mechanical activity of the heart as well as the hemodynamic parameters [3,14,15], we did not measure any other parameters of the hearts into this study.…”
Section: Effects Of Either Antioxidants or Doxycycline Treatments On supporting
confidence: 85%
“…We demonstrated for the first time that a MMP-2 inhibitor doxycycline has beneficial role on cardiac dysfunction via affecting Ca 2? signaling in streptozotocin (STZ)-induced diabetic rat model [14]. Previoulsy, we have also showed that either sodium selenite or a long chain (n-3) polyunsaturated fatty acid treatment protected heart against diabetes-induced cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies have also shown that doxycycline has some ability to inhibit reactive oxygen species (ROS) [24]. Although we cannot exclude the possibility that doxycycline may have other protective effects because of its reported pleiotropic actions including inhibition of proinflammatory cytokines and ROS, it is plausible that, to the plasma concentration achievable with the dose of doxycycline used in our study [13], MMP inhibition, as opposed to ROS scavenging, may be the main mechanism of its protective action [25]. Results of preclinical studies show that the use of doxycycline in the first 7 days post-MI may exert a cardioprotective effect reducing LV remodeling [14,15] and infarct size [26][27][28].…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies (31,38,45) have consistently shown that steady-state I to density and the fast component of I to recovery are reduced in animal models of T1DM. As for heterogeneity of the impact of T1DM on I to , Shimoni et al (31) showed that the difference in I to between streptozotocin-induced diabetic rats and nondiabetic control rats was larger in Epi than in Endo myocytes.…”
Section: Discussionmentioning
confidence: 88%
“…However, knowledge of electrical remodeling in the heart by type 2 DM (T2DM) is very limited. Most of the earlier studies used models of type 1 DM (T1DM; i.e., streptozotocin-induced and alloxan-induced diabetes) and showed that the action potential (AP) duration (APD) was prolonged and that the transient outward K ϩ current (I to ), L-type Ca 2ϩ current (I Ca,L ), and inward rectifier K ϩ current (I K1 ) were reduced in T1DM (31,38,45). However, it remains unclear whether T2DM induces the same electrical remodeling as that induced by T1DM.…”
mentioning
confidence: 99%